2020
DOI: 10.1039/c9nr10943a
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo-like nitrogen-doped porous carbon nanofibers encapsulated nickel–cobalt alloy nanoparticles composite material derived from the electrospun fiber of a bimetal–organic framework as efficient bifunctional oxygen electrocatalysts

Abstract: Bamboo-like nanofibers NiCo-0.8@N-CNFs-800 demonstrated an excellent bifunctional electrocatalytic performance, with a low reversible overpotential of 0.79 V between the ORR (E1/2) and OER (Ej = 10 mA cm−2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Bi‐ or multimetal nanomaterials are not only be regarded as efficient HER electrocatalysts but also OER electrocatalysts 141,148‐155 . A typical example is the PdNi nanoparticles encapsulated in CNFs (PdNi/CNFs) for both HER and OER applications 141 .…”
Section: Electrocatalytic Water Splitting Based On the Electrospun Namentioning
confidence: 99%
See 1 more Smart Citation
“…Bi‐ or multimetal nanomaterials are not only be regarded as efficient HER electrocatalysts but also OER electrocatalysts 141,148‐155 . A typical example is the PdNi nanoparticles encapsulated in CNFs (PdNi/CNFs) for both HER and OER applications 141 .…”
Section: Electrocatalytic Water Splitting Based On the Electrospun Namentioning
confidence: 99%
“…Bi-or multimetal nanomaterials are not only be regarded as efficient HER electrocatalysts but also OER electrocatalysts. 141,[148][149][150][151][152][153][154][155] A typical example is the PdNi nanoparticles encapsulated in CNFs (PdNi/CNFs) for both HER and OER applications. 141 The size and uniformity of the PdNi nanoparticles could be tuned by adjusting the molar ratio of the metal precursors.…”
Section: Multimetallic Effectsmentioning
confidence: 99%
“…Given the rapid growth of the global energy demand and increasingly severe pollution of the environment, the development of highly efficient materials and technologies for energy storage and conversion is of great signicance. [1][2][3] Among various technologies developed, Zn-air batteries have proven a promising battery system owing to the high theoretical energy density, the appropriate operating voltage ($1.65 V), abundant zinc resources, and free supply of oxygen for the air cathode. [4][5][6] However, the inherent sluggish kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), which are the basis of Zn-air batteries, 7 have hampered its development and applications.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12][13][14][15][16][17][18] In this regard, metal-organic framework (MOF)-based catalysts have become the focus of electrocatalyst design, given its remarkable advantages including the porous structure, the existence of abundant transition metal, and the easy modication of architecture and composition. 1,15,[19][20][21] Moreover, the evenly dispersed metal species in the MOFderived materials are able to function as active sites for electrochemical reactions. 12,[22][23][24] It has been reported that Co-based MOF electrocatalysts have shown good catalytic activity, while the dissatisfactory bifunctional ORR/OER property, 25,26 the poor electrical conductivity, and aggregation of nanoparticles 19 still limit their practical application in Zn-air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Though the state-of-the-art precious-metal-based catalysts including IrO 2 and RuO 2 show impressive OER activities, the scarcity and high cost hinder their scale-up deployment [8][9][10]. Therefore, it is of great significance to develop earth-abundant transition metals (especially Fe, Co, and Ni) and their derivatives as highly efficient electrocatalysts for oxygen evolution [11][12][13][14][15][16][17][18][19][20][21][22]. Among the non-noble metal-based electrocatalysts, transition metal oxides (TMOs) and layered doublehydroxides (LDHs) have been well designed with satisfying OER activities [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%